Development and Evaluation of Alprazolam Controlled Release tablets - Shrestha, Sarmila; Khanal, Dharma Prasad; Thapa, Panna (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
Twenty three different tablet formulations of alprazolam were prepared using Polymer like hydroxypropylmethyl cellulose (HPMC K4M, HPMC K15M and HPMC K100M) in the concentration of 5 – 50 % of total weight of tablets and combination of HPMC K15M and HPMC K100M with ethyl cellulose (EC) was formulated by using wet granulation method. Drug formulation containing 1.0 mg, 1.5 mg, 5 mg, 10 mg and 15 mg alprazolam per tablet maintaining constant HPMC K15M concentration was also developed. The in-vitro dissolution studies of the formulated and marketed product in USP type II apparatus showed that the drug release is dependent upon the drug: polymer ratio; also molecular weight of the polymer and solubility of loaded drug. With increasing concentration and molecular weight of polymer, drug release was found to be decreased. When formulating the tablets the method used whether direct compression or wet granulations also affect the release of the drug from matrix. Wet granulation method by using 40 % HPMC K15M in combination with 5 % EC was found to be most suitable controlled release alprazolam tablet as drug release was found to be appreciable in this formulation. When loading dose of alprazolam was increased, drug release was found to be tremendously decreased because of the poor solubility of alprazolam in water. When one-way ANOVA was applied for various formulated and marketed tablets it was found that there is no significant difference (p > 0.05) in drug release rate among formulation similarly model independent methods was also applied such as similarity and dissimilarity factor and found that there is no significant difference between these formulations. DOI: http://dx.doi.org/10.3126/jmmihs.v1i1.9896 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(1) 2011; 8-23